Entradas biológicas de nitrógeno en un bosquete ribereño : análisis del ARA - Péres Hernández M.C.; Gutiérrez Mañero F.J.; Pozuelo González J.-M.; Bermúdez de Castro F. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
An annual acetylene-reducing activity (ARA) pattern in a riparian forest is determined. Free microorganisms, legumes and Alnus glutinosa shrubs and trees were measured in spring, summer, autumn and winter. The studied nitrogen-fixing systems present different ARA rates. Maximum ARA is found in October for free microorganisms, in July for alder shrubs and in November for alder trees and legumes. This biologically fixed nitrogen, when released into the environment, will represent an easily available source of nitrogen for other organisms in the surroundings.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)